Introducing extreme data storage middleware of schema-free document stores using MapReduce. (2015) - Ma, Kun; Yang, Bo
Data warehousing has been embraced by organisations of all sizes. However, there are few publications on data warehouse of NoSQL. In this paper, an extreme data storage middleware (EDSM) of schema-free document stores using MapReduce is presented to address the issue of formulating no redundant data warehouse with small amount of storage space for the purpose of their composition in a way that utilises the MapReduce framework. The experiment is shown to successfully build the NoSQL data warehouse reducing data redundancy compared with document with timestamp and lifecycle tag solutions. Our experiment also provides insight into some of the key challenges and shortcomings that researchers and engineers face when designing the data warehouse middleware.